2014
DOI: 10.14405/kjvr.2014.54.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulence and cytolethal distending toxin (CDT) genes in thermophilic Campylobacter spp. from dogs and humans in Gyeongnam and Busan, Korea

Abstract: : The prevalence of thermophilic Campylobacter (C.) spp. in stray, breeding, and household dogs was 25.2, 12.0, and 8.8%, respectively. C. jejuni and C. upsaliensis were the predominant Campylobacter spp. from household dogs. cdtA, cdtB, and cdtC were detected by PCR in all isolates. Despite the high cytolethal distending toxin (CDT) gene prevalence, only 26 (31%) C. jejuni strains and one (15.3%) C. coli strain showed evidence of CDT production in HEp-2 cell cytotoxicity assays. Virulence-associated genes det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
1
1
0
1
Order By: Relevance
“…Relatively similar results were obtained in Egypt by [32] who confirmed these results with gene expression of dnaJ and using 23srR-NA as a housekeeping gene. On the other hand our results in human samples agreed with [20] who detected dnaJ gene in 46% and 50% of human C. jejuni and C. coli samples respectively although there are some differences in results of dnaJ from chicken samples which came in a rate of 69% and 70% for C. jejuni and C. coli respectively [33], detected dnaJ gene in 100% of Human C. jejuni and C. coli. High detection of dnaJ gene in chicken than human host that reported by many authors confirmed the data that revealed importance of dnaJ gene in broiler cecal colonization by [34].…”
Section: Am J Biomed Sci and Ressupporting
confidence: 86%
“…Relatively similar results were obtained in Egypt by [32] who confirmed these results with gene expression of dnaJ and using 23srR-NA as a housekeeping gene. On the other hand our results in human samples agreed with [20] who detected dnaJ gene in 46% and 50% of human C. jejuni and C. coli samples respectively although there are some differences in results of dnaJ from chicken samples which came in a rate of 69% and 70% for C. jejuni and C. coli respectively [33], detected dnaJ gene in 100% of Human C. jejuni and C. coli. High detection of dnaJ gene in chicken than human host that reported by many authors confirmed the data that revealed importance of dnaJ gene in broiler cecal colonization by [34].…”
Section: Am J Biomed Sci and Ressupporting
confidence: 86%
“…is cytolethal-distending toxin (CDT), encoded by the three adjacent genes cdtA, cdtB, and cdtC [49]. The carriage of cdt complex is common in isolates from poultry [49], swine [45], cattle [50], and human [30,51] isolates. In the present study, it was found that 46.7% of wildlife waterfowl isolates possessed three cdt genes.…”
Section: Discussionmentioning
confidence: 99%
“…Este patógeno presenta una serie de factores de virulencia responsables del proceso de fisiopatogenia como ser los genes flaA, cadF, racR y dnaJ responsables de la expresión de la adherencia y colonización; los genes virB, ciaB y pldA que participan en la invasión, los genes ctdB, ctdC, citotoxinas de distensión, que evitan en las células eucariotas que entren en mitosis, conduciendo a la muerte celular y wlaN, indicado como el gen involucrado en la expresión de mimics de gangliosidos en el síndrome de Guillain Barre (16)(17)(18)(19) .…”
Section: Introduccionunclassified